2021
DOI: 10.1111/phn.12923
|View full text |Cite
|
Sign up to set email alerts
|

E‐learning cultural competence for public health workers: A feasibility and pilot study

Abstract: Objective To describe the development, feasibility, and preliminary efficacy of a seven‐module e‐learning for enhancing cultural competence of public health workers. Design The study was based on the framework of the new Medical Research Council; a mixed methods design was used. Sample A four‐week pilot cluster‐randomized controlled trial was conducted with 39 public health workers and 74 migrants in South Korea. Feasibility and preliminary efficacy were assessed according to initiation, retention, adherence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A systematic review reported that cultural competence education was mainly offered through traditional face-to face teaching to participants (Oikarainen et al, 2019). Recent studies have demonstrated the effectiveness of cultural competence training using online or technological methods, such as Facebook-based education for healthcare students (Chang et al, 2017), e-learning for public health workers (Chae et al, 2021), web-based education for palliative care nurses (Bhat et al, 2015), and mobile applications for RNs (Sung & Park, 2021). As such, online learning programs could be a useful strategy for improving clinical skills under time restrictions for health professionals, such as nurses during the COVID-19 pandemic or night shifts (Al-Mugheed et al, 2022; Slobodin et al, 2021; Wilson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported that cultural competence education was mainly offered through traditional face-to face teaching to participants (Oikarainen et al, 2019). Recent studies have demonstrated the effectiveness of cultural competence training using online or technological methods, such as Facebook-based education for healthcare students (Chang et al, 2017), e-learning for public health workers (Chae et al, 2021), web-based education for palliative care nurses (Bhat et al, 2015), and mobile applications for RNs (Sung & Park, 2021). As such, online learning programs could be a useful strategy for improving clinical skills under time restrictions for health professionals, such as nurses during the COVID-19 pandemic or night shifts (Al-Mugheed et al, 2022; Slobodin et al, 2021; Wilson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…E-learning enables teachers to represent the information using media in the form of text, images, animation, video, and audio [41,42] (Figure 2). Over the last decades, e-learning has rapidly expanded in medical education, health promotion, patients, and medical education that take advantage of a useful networking flow and flexibility of the communication system [33][34][35]. Moreover, healthcare education faces higher challenges determined by an increase in students' access to post-degree courses and specialisation that requires novel strategies to improve the quality of the scholarship and the didactic level [35][36][37].…”
Section: Introductionmentioning
confidence: 99%